THE DYNAMICS OF LANDSCAPE PATTERN CHANGES IN MINING AREAS: THE CASE STUDY OF THE ADAMÓW-KOŹMIN LIGNITE BASIN - Fagiewicz, Katarzyna (Quaestiones Geographicae, 2019)
Mining belongs to the types of human activity that have a significant impact on the environment, and especially on the landscape. The main objective of this study is a quantitative diagnosis of the dynamics of land use changes and landscape pattern modification in areas shaped under the influence of processes related to the open pit exploitation of lignite. The study was carried out in the Adamów-Koźmin Lignite Basin, which is a model example of an area affected by strong anthropogenic pressure. An assessment of changes was carried out using a set of maps depicting land use in the period preceding the exploitation of lignite (the year 1940) and after over 60 years of the mining activity in this area (as of 2011). The source materials for mapping for the first period were archival maps and for the second period, an orthophotomap. The heads-up digitising method was used to determine 7 types of land-cover classes according to the definitions of Corine Land Cover. Ten landscape metrics for five categories of landscape features (surface, shape, neighbourhood, edge, spatial distribution and diversity) were used in the landscape pattern analysis. The results do not confirm the hypothesis of a significant landscape simplification after reclamation. The shape of patches in the landscape was more complex and the number of land-use types was higher, which combined with their spatial arrangement, caused the landscape pattern to be more diversified in the year 2011.